Knowledge science, engineering and management 5th International Conference, KSEM 2011, Irvine, CA, USA, December 12-14, 2011. Proceedings - Xiong, Hui; Lee, W. B. (Lecture notes in computer science, 2011)
This book constitutes the proceedings of the 5th International Conference on Knowledge Science, Engineering and Management, KSEM 2011, held in Irvine, CA, USA, in December 2011. The 34 revised full papers presented together with 7 short papers were carefully reviewed and selected from numerous submissions.